Proteomic Approaches to Defining Remission and the Risk of Relapse in Rheumatoid Arthritis - O’Neil, Liam J.; Hu, Pingzhao; Liu, Qian; Islam, Md. Mohaiminul; Spicer, Victor; Rech, Juergen; Hueber, Axel; Anaparti, Vidyanand; Smolik, Irene; El-Gabalawy, Hani S.; Schett, Georg; Wilkins, John A. (Frontiers in Immunology, 2021)
ABSTRACT Objectives Patients with Rheumatoid Arthritis (RA) are increasingly achieving stable disease remission, yet the mechanisms that govern ongoing clinical disease and subsequent risk of future flare are not well understood. We sought to identify serum proteomic alterations that dictate clinically important features of stable RA, and couple broad-based proteomics with machine learning to predict future flare. Methods We studied baseline serum samples from a cohort of stable RA patients (RETRO, n = 130) in clinical remission (DAS28<2.6) and quantified 1307 serum proteins using the SOMAscan platform. Unsupervised hierarchical clustering and supervised classification were applied to identify proteomic-driven clusters and model biomarkers that were associated with future disease flare after 12 months of follow-up and RA medication withdrawal. Network analysis was used to define pathways that were enriched in proteomic datasets. Results We defined 4 proteomic clusters, with one cluster (Cluster 4) displaying a lower mean DAS28 score (p = 0.03), with DAS28 associating with humoral immune responses and complement activation. Clustering did not clearly predict future risk of flare, however an XGboost machine learning algorithm classified patients who relapsed with an AUC of 0.80 using only baseline serum proteomics. Conclusions The serum proteome provides a rich dataset to understand stable RA and its clinical heterogeneity. Combining proteomics and machine learning may enable prediction of future RA disease flare in patients with RA who aim to withdrawal therapy.